Restoration of the function of the sciatic nerve and its branches after trauma - Alimkhan Khalimov; Yermek Dyussembekov; Marat Mirzabaev; Marat Aliyev; Nursultan Abilkhanov; Daniyar Bayezov; Saule Iskakova; Aigul Tazhiyeva (Medicinski glasnik, 2025)
Aim: To investigate the efficacy of various methods for restoring the sciatic nerve and its branches after traumatic injuries to develop optimal treatment strategies, improve functional outcomes, and enhance patients' quality of life. Methods: A retrospective cohort study was conducted at the Neurosurgical Centre of Almaty, Kazakhstan, based on City Clinical Hospital No. 7. From 2013 to 2022, 227 patients with sciatic nerve lesions and their branches were operated. The proportion of patients of working age was 93.8%. Over half of the patients were hospitalized more than six months after the injury. Results: A high and satisfactory level of functional recovery after the surgical treatment of the sciatic nerve and its branches was achieved in 173 (77.5%) patients, with partial improvement in 21 (9.4%) and no significant improvement in 30 (13.1%). Two-stage restoration of the sciatic nerve function in cases with diastasis of more than 5 cm improved treatment results in 202 (89.2%) patients contributing to the restoration of motor function and gait within two to three years. Conclusion: When repairing the sciatic nerve with extensive defects, the tibial nerve is prioritized over the peroneal nerve due to better regeneration. Nerve autoplasty is preferred because of the rigidity of the sciatic nerve trunk and significant muscle load. For diastasis over 7 cm, the peroneal nerve trunk can be used for tibial nerve plasty. Two-stage reconstruction involves tendon-muscle plasty after signs of tibial nerve conduction appear, restoring motor function and gait and improving the patient's quality of life.
Keywords: nerve regeneration; nerve transfer; peripheral nerve injuries; sciatic nerve